The Effect of Full Day School Implementation on Learning Motivation of Elementary School Students - Yantoro, Yantoro; Muspawi, Mohamad; Shalahudin, Shalahudin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to analyze an effect of the implementation of full day school on learning motivation of elementary school students. The research method used is a mixed research method with explanatory design. The number of samples used were 174 students. The research data were obtained by distributing a full day school application questionnaire and a student learning motivation questionnaire, as well as conducting interviews with students. Furthermore, the data were analyzed quantitatively with simple regression type and inferential statistics. The results showed that has been done, it can be concluded that the implementation of full day and student motivation in Elementary School is already in a good category. This is reinforced by the results of interviews which show that through the implementation of full day school it can have a positive impact, namely that student creativity can be more developed, achievement increases, and students can develop their talents and skills through extracurricular activities, which can then be developed. Make it easier for teachers to deliver material to students because of the time. which is old. Based on the hypothesis test conducted, it was found that there was an influence between the implementation of full day school on student learning motivation in elementary schools, with the percentage contribution of the influence of 61.3% to the dependent variable, and 39.7% influenced by other variables.